Does the Belt and Road Initiative reduce smog pollution in key provinces along the route? - Jiang, Jingao; Wu, Maoguo (Frontiers in Environmental Science, 2024)
Introduction: This study investigated the impact of the Belt and Road Initiative (BRI) on reducing smog pollution in key provinces along the route. Utilizing data from 284 prefecture-level cities in China from 2007 to 2018, this study adopted a propensity score matching-difference-in-differences approach, and conducted a series of robustness checks. The results indicate that the BRI has overall reduced particulate matter with aerodynamic diameter less than 2.5 µm (PM2.5) levels in key provinces along the route, and robustness checks find consistent results. Dynamic effect tests reveal a significant reduction in the annual average PM2.5 levels in key provinces along the route after the BRI was implemented in 2014. Tests on underlying mechanism find that the BRI mainly reduced PM2.5 levels in key provinces along the route by promoting technological innovation and optimizing industrial structure. Furthermore, heterogeneity tests find that the BRI significantly reduced PM2.5 levels only in cities of key provinces along the Silk Road Economic Belt, with variations in significance due to regional differences, city administrative levels, and marketization. In addition, the BRI has enhanced green total factor productivity in key provinces along the route by reducing PM2.5 levels. This study enriches research on the economic consequences of the BRI in terms of environmental protection, and also provides empirical support for the construction of the green "Belt and Road".